SOLITON SOLUTIONS FOR NON-LINEAR KUDRYASHOV'S EQUATION VIA THREE INTEGRATING SCHEMES - Arshed, Saima; Mirhosseini-Alizamini, Mehdi; Baleanu, Dumitru; Rezazadeh, Hadi; İnç, Mustafa; Hussain, Majid (Vinca Inst Nuclear Sci, 2021)
This paper considers the non-linear Kudryashov's equation, that is an extension of the well-known dual-power law of refractive index and is analog to the generalized version of anti-cubic non-linearity. The model is considered in the presence of full non-linearity. The main objective of this paper is to extract soliton solutions of the proposed model. Three state-of-the-art integration schemes, namely modified auxiliary equation method, the sine-Gordon expansion method and the tanh-coth expansion method have been employed for obtaining the desired soliton solutions.
Keywords: soliton solution; Kudryashov's equation; analytical methods